(untitled) (Asian Education Studies, 2017)
Achieving equity and excellence for all young people remains the major challenge of education systems across the world. This paper contends that equity and excellence for students currently underserved by our system needs transformative school reform. In response, we outline the ako: critical contexts for change. This model has been applied across five dimensions for transformative reform within Kia Eke Panuku (Note 2). This paper focuses on how this model can be understood and applied alongside curriculum implementation. We draw evidence from wider research of the impact on improving student achievement when individual aspects of the ako: critical contexts for change have been applied. We have found that when all three contexts are applied simultaneously and spread throughout the school, pedagogical reform can be accelerated, even for those students most underserved.